Build for change : - Trefler, Alan (John Wiley & Son, Inc, 2014)
Consumers have more options than ever before, and ensuring customer loyalty in the modern market means knowing exactly what the customer wants and how to deliver it brilliantly. Build For Change provides actionable guidance for engaging this new connected consumer.